Estimasi Biaya Perangkat Lunak Pada Aplikasi SIBIMA Universitas XYZ dengan Menggunakan Metode Function Point - Sandhea, Annisa Azzar; Maulidiyah, Sri; Sari, Renny Dewi (STMIK Budi Darma, 2020)
The growing development of computers triggers the amount of software in different amounts and uses. A system is said to be good when starting planning that can estimate the cost, time and amount of resources needed as a basis for planning a system. So that the estimated cost can be an element in an assessment. The research explains that the Academic Guidance Information System (SIBIMA) which is a system for carrying out student consultation activities with academic advisers at XYZ University. From the software cost estimation results at SIBIMA use Function Point which is a method of estimating software size using an indirect approach or indirect approach to estimate software size in Function Point units (FP), for Effort values on SIBIMA is 379,906 man / hour and it is known that the cost needed in developing SIBIMA is IDR 22,858,705 so that it can be used as a reference if the higher education institution wants to develop a software system